ANDREAS VOLANUS’ SWITCHES AND SPURS: TAMING A HERESY - Petuchovaitė, Gintarė (Literatūra, 2013)
The author stresses that the royal secretary Andreas Volanus (about 1531–1610), ideologist of the Evangelical Reformed in the Grand Duchy of Lithuania, had polemics not only with Catholics, but also with Antitrinitarians. His literary polemic with Antitrinitarians lasted for about a half of the 16th century. This article argues that Volanus considered radical Reformation movement as heretical. Therefore, the article attempts to summarize the concept of heresy (non-compliance with early Church teaching, novelty of opinions, fallibility of fabrication, a variety of ideas, hypocrisy, distortion of the sola scriptura principle). The article asserts that Volanus tried to repress radical, destructive ideas by switches and spurs – by a strict and orthodox Swiss doctrine (Confessio helvetica posterior, 1566). In this article, text of Volanus – dedication to Ioanni Schemeto, a nobleman of Samogitia, from the last work of polemic Epistolae aliquot ad refellendum doctrinae Samosatinianae errorem, ad astruendam Orthodoxam de Divina Trinitate sententiam, hoc tempore lectu non inutiles (1592) – is presented and commented. This text reveals Volanus’ position and his attitudes to heresy.